THE IMPACT OF THE COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) ON ACADEMIC READING SKILLS: THE CASE OF FIRST-YEAR EFL STUDENTS AT BATNA 2 UNIVERSITY - Ahmed Gaid, Oussama (Armenian Folia Anglistika, 2025)
This present study investigated the impact of the Cognitive Academic Language Learning Approach (CALLA) on academic reading skills among first-year English as a Foreign Language (EFL) students at Batna 2 University. Over a 15-week intervention period during the 2024-2025 academic year, the study used a quasi-experimental design with two student groups (n = 50) and control (n = 50) groups. Results suggested statistically significant improvements in reading comprehension (p < .001, Cohen's d = 1.82), vocabulary acquisition, as well as metacognitive strategy use among the experimental group. The experimental group showed notable gains from a pre-test mean of 12.4 to a post-test mean of 19.8, whereas the control group showed minimal gains (12.6 to 13.1). A strong positive relationship was revealed, by means of correlation analysis, between metacognitive strategy use and reading performance (r = .72, p < .001). Findings substantiate the efficacy of the CALLA model in enhancing EFL reading skills and advocate for its integration into EFL curricula to foster meaningful comprehension and metacognitive awareness. Study results match prior research on strategy-based instruction and seek to offer insights into the growing body of literature on the role of explicit strategy instruction in academic language learning contexts.
Keywords: CALLA; academic reading; EFL; strategy-based instruction; metacognition; reading comprehension